Atrial Fibrillation Burden and Short-Term Risk of Stroke: Case-Crossover Analysis of Continuously Recorded Heart Rhythm From Cardiac Electronic Implanted Devices. (October 2015) - Turakhia, Mintu P.; Ziegler, Paul D.; Schmitt, Susan K.; Chang, Yuchiao; Fan, Jun; Than, Claire T.; Keung, Edmund K.; Singer, Daniel E.
Abstract : Background—: The temporal relationship of atrial fibrillation (AF) and stroke risk is controversial. We evaluated this relationship via a case-crossover analysis of ischemic strokes in a large cohort of patients with cardiac implantable electronic devices. Methods and Results—: We identified 9850 patients with cardiac implantable electronic devices remotely monitored in the Veterans Administration Health Care System between 2002 and 2012. There were 187 patients with acute ischemic stroke and continuous heart rhythm monitoring for 120 days before the stroke (age, 69±8.4 years; 98% with an implantable defibrillator). We compared each patient's daily AF burden in the 30 days before stroke (case period) with their AF burden during days 91 to 120 pre stroke (control period). Defining positive AF burden as ≥5.5 hours of AF on any given day, 156 patients (83%) had no positive AF burden in both periods and, in fact, had little to no AF; 15 (8%) patients had positive AF burden in both periods. Among the discordant (informative) patients, 13 exceeded 5.5 hours of AF in the case period but not in the control period, whereas 3 had positive AF burden in the control but not in the case period (warfarin-adjusted odds ratio for stroke, 4.2; 95% confidence interval, 1.5–13.4). Odds ratio for stroke was highest (17.4; 95% confidence interval, 5.39–73.1) in the 5 days immediately after a qualifying occurrence of AF and decreased toward 1.0 as the period after the AF occurrence increased beyond 30 days. Conclusions—: In this population with continuous heart rhythm recording, multiple hours of AF had a strong but transient effect raising stroke risk. Abstract : Supplemental Digital Content is available in the text.